HUBUNGAN PERSEPSI PADA PELAJARAN FISIKA DENGAN TINGKAT STRES SISWA DI SMA NEGERI 1 NANUSA TALAUD - Tatuwo, Meini; Palandeng, Henry; Bawotong, Jeavery (JURNAL KEPERAWATAN, 2014)
Abstrack :Perception is a process that is applied the knowledge in the past to collect and construe the stimulate which is listed by part of senses. Perception toward Physics lesson give an impact to the phase of stress in study. One of the factor which is influence the student’s perception in Physics lesson is the less of basic knowledge of Physics lesson caused by lack of Physics teacher. The Purpose of this study is to know the relationship between perception of Physics lesson with the phase of stress among student in SMA Negeri 1 Nanusa. The Methods of this research was using random Sampling (sampel acak) while the population in this research is everyo student in SMA Negeri 1 Nanusa, the sample in this research are 59 persons. The Statistical Test is using the Chi-square test with the significant level 95% = á 0,05. The Study Result of this research was found that the level of confidence 95% shows the value of p= 0,022. The value of p is smaller than the value of á = 0,05. The Conclusions of this research : there is a significant relationship between perception in Physics lesson with the phase of stress among student that the value (p = 0,022 á 0,05). Keywords:Perception, phase of stress among student. Abstrak : Persepsi adalah proses yang memanfaatkan pengetahuan sebelumnya untuk mengumpulkan dan memaknakan stimuli yang telah didaftar oleh organ penginderaan. persepsi terhadap pelajaran fisika sangat mempengaruhi tingkat stres siswa dalam belajar. Salah satu faktor yang mempengaruhi persepsi siswa pada pelajaran fisika adalah kurangnya dasar tentang pelajaran fisika pada siswa karena tidak adanya guru bidang studi.Tujuan Penelitian ini untuk mengetahui hubungan persepsi pada pelajaran fisika dengan tingkat stres siswa di SMA Negeri 1 Nanusa. Metode Penelitian menggunakan metode cross sectional. Teknik Pengambilan Sampel yaitu teknik random Sampling (sampel acak) sedangkan populasi dalam penelitian ini adalah seluruh siswa SMA Negeri 1 Nanusa, sampel dalam penelitian ini sebanyak 59 orang. Uji Statistikmenggunakanuji Chi-Squaredengan tingkat kemaknaan 95% = á 0,05.Hasil Penelitianyang didapat pada tingkat kepercayaan 95% menunjukkan nilai p=0,022. Nilai p ini lebih kecil dari nilai á = 0,05.Kesimpulan penelitian: terdapat hubungan yang signifikan antara persepsi pada pelajaran fisika dengan tingkat stres siswa dengan nilai yang diperoleh (p = 0,022 á 0,05). Kata kunci : Persepsi, Tingkat Stres, Siswa